Modular kit to support stem-based electronic learning (2023)
This project focuses on the creation of an electronics educational kit designed for non-tertiary higher education students. The kit encompasses essential topics such as the Wheatstone bridge, signal filtering, and the use of transistors for amplification. These are all crucial subjects in electronics to enhance understanding of circuit design and electronic systems. The proposed kit incorporates blocks that use a magnetic union to connect the pins and thus assemble the modules. This design enables students to interact with them and learn about the aforementioned topics. Additionally, the kit includes simulations conducted using the Every Circuit software to aid visualization of module operation. There's also an application to activate the module to be used. Aiming for feedback, a proof of concept was conducted to assess the efficacy of the kit on 11 students, and 3 students performed a pre and post-evaluation of one of the designed practices. This feedback allowed us to make improvements and refine the materials created. Achieving in this way, after two versions, a final functional prototype with favorable results after the student's evaluation. The idea is to support the learning process by focusing on core concepts and providing students with material to bolster their independent learning. By promoting STEM education and fostering logical, critical thinking, we aim to bring new tools to navigate the challenges of the new generation. Through our efforts, we strive to cultivate a generation of individuals with the essential skills needed to thrive in our science and technology-driven society.